Polyimide laminate

JP7936710B2Active Publication Date: 2026-10-16KANEKA CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022178553
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-11-08
Publication Date
2026-10-16
Estimated Expiration
2042-11-08

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、デスミア処理条件を強めた際に発生する層間のクラックを抑制できるポリイミド積層体を提供することができる。具体的には、本発明に係るポリイミド積層体によれば、配線板の製造工程において工数を増やすことなく、レーザー加工後のデスミア処理時においてビア内壁のクラックの発生を抑制できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007936710000007
    Figure 0007936710000007
  • Figure 0007936710000008
    Figure 0007936710000008
  • Figure 0007936710000001
    Figure 0007936710000001
Patent Text Reader

Abstract

To provide a polyimide laminate which can further suppress interlayer cracks which occur when desmear treatment conditions are made more severe.SOLUTION: Provided is a polyimide film laminate having a thermoplastic polyimide layer arranged on at least one surface of a non-thermoplastic polyimide, where a single layer of the non-thermoplastic polyimide has an elastic modulus of 5-12 GPa according to tensile testing, a 10% distortion stress of 190-310 MPa, and a linear expansion coefficient of 5-20 ppm / °C, and a compatibility parameter (a square value of the SP value difference) of 5.0 J / cm3 or less, and the thermoplastic polyimide has a linear expansion coefficient of 65 ppm / °C or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a polyimide film laminate with excellent crack resistance. [Background technology]

[0002] In recent years, demand for flexible printed circuit boards (hereinafter referred to as "FPCs") has been growing along with the expanding demand for electronic products, mainly smartphones and laptop computers. Among these, FPCs that use polyimide film laminates containing a thermoplastic polyimide layer as an adhesive layer are expected to see further demand growth due to their excellent heat resistance and flexibility. Furthermore, in recent years, electronic devices have become lighter, smaller, and thinner, and the demand for miniaturization of FPC wiring remains strong.

[0003] When manufacturing micro-double-sided or multilayer FPCs, it is common to use a metal-clad laminate, which is made by laminating metal foil such as copper foil to both sides of a polyimide film, as the material. In FPC manufacturing, the first step is to create holes (hereinafter referred to as "vias") to allow for conductivity between layers. By plating the inner walls of the vias, conductivity can be made between both sides of the wiring board. There are two methods for via formation: the through-hole method, which involves drilling through holes in the metal foil and insulating layer (polyimide layer) on both sides using a drill or laser, and the blind via method, which involves cutting the metal foil and insulating layer on one side with a laser, leaving the metal foil on the other side intact. In particular, the blind via method is frequently used in micro-FPCs to make efficient use of the area.

[0004] Conventionally, in such via formation processes, a wet desmear treatment is performed after drilling, in which the laminate is treated with an alkaline potassium permanganate aqueous solution or the like under heating to clean the inside of the holes and the surface of the metal foil and to remove resin residue. Polyimide is easily hydrolyzed under alkaline conditions, and when laser processed, localized heating generates residual stress, making it prone to defects such as cracks in the inner walls of vias during the desmear treatment after the via formation process. Patent Document 1 describes a method for reducing the storage modulus at 380°C in a dynamic viscoelastic test of a multilayer polyimide film to less than 0.350 MPa, thereby removing residual stress generated by laser processing and suppressing the occurrence of defects. [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] International Publication No. 2022 / 014257 [Overview of the Initiative] [Problems that the invention aims to solve]

[0006] However, the desmear conditions in Patent Document 1 were relatively weak, and there was room for further improvement in suppressing the crack occurrence rate between the non-thermoplastic polyimide layer and the thermoplastic polyimide layer when the desmear treatment conditions were strengthened. The present invention aims to provide a polyimide laminate that can suppress interlayer cracks that occur when the desmear treatment conditions are strengthened. [Means for solving the problem]

[0007] As a result of diligent research, the inventors have found that the above problems can be overcome with the following configuration.

[0008] [1] A polyimide laminate comprising a thermoplastic polyimide layer on at least one side of a non-thermoplastic polyimide, wherein the non-thermoplastic polyimide single layer has an elastic modulus of 5 to 12 GPa, a 10% strain stress of 190 to 310 MPa, and a coefficient of linear expansion of 5 to 20 ppm / °C as determined by tensile testing, and the compatibility parameter (square of the SP value difference) between the non-thermoplastic polyimide and the thermoplastic polyimide is 5.0 J / cm 3 The following polyimide film laminate is characterized in that the coefficient of linear expansion of the thermoplastic polyimide is 65 ppm / °C or less.

[0009] [2] The polyimide film laminate according to claim 1, characterized in that the aromatic diamine used in the production of the non-thermoplastic polyimide comprises 2,2'-dimethylbiphenyl-4,4'-diamine, and the acid dianhydride comprises 3,3',4,4'-benzophenonetetracarboxylic dianhydride and / or 3,3',4,4'-biphenyltetracarboxylic dianhydride. [Effects of the Invention]

[0010] The present invention provides a polyimide laminate that can suppress interlayer cracks that occur when desmear treatment conditions are strengthened. Specifically, the polyimide laminate according to the present invention can suppress the occurrence of cracks in the inner walls of vias during desmear treatment after laser processing without increasing the number of steps in the manufacturing process of the printed circuit board. [Brief explanation of the drawing]

[0011] [Figure 1] This figure shows an example of a polarized microscope image used for actual discrimination according to the present invention, in which no cracks were determined to have occurred. [Figure 2] This figure shows an example of a polarized microscope image in which crack formation was determined to be present, which was used for actual discrimination according to the present invention. [Modes for carrying out the invention]

[0012] Preferred embodiments of the present invention will be described in detail, but the present invention is not limited thereto. All academic and patent documents cited herein are incorporated herein by reference. Unless otherwise specified herein, "A to B" representing a numerical range means "A or greater (including A and greater than A) to B or less (including B and less than B)."

[0013] The laminate of the present invention is a polyimide laminate in which a thermoplastic polyimide layer is provided on at least one side of a non-thermoplastic polyimide. The non-thermoplastic polyimide single layer has an elastic modulus of 5 to 12 GPa, a 10% strain stress of 190 to 310 MPa, and a coefficient of linear expansion of 5 to 20 ppm / °C as determined by tensile testing, and the compatibility parameter (square of the difference in SP values) between the non-thermoplastic polyimide and the thermoplastic polyimide is 5.0 J / cm 3 The following is a polyimide film laminate characterized in that the coefficient of linear expansion of the thermoplastic polyimide is 65 ppm / °C or less.

[0014] Patent Document 1 has shown that hole cracks can be suppressed by reducing the residual stress in dynamic viscoelastic testing of the non-thermoplastic polyimide layer. However, cracks tend to occur at the interface between the non-thermoplastic and thermoplastic polyimide layers when the desmear treatment conditions are strengthened. In order to further improve reliability during via and plating processes at FPC manufacturers, the inventors of this invention have conducted diligent research and have found that interfacial compatibility can be improved by reducing the difference in solubility parameters between the non-thermoplastic and thermoplastic polyimide layers, thereby suppressing interfacial cracks during laser processing.

[0015] <Elements of polyimide laminates> (Non-thermoplastic polyimide layer) From the viewpoint of dimensional stability of FPC, the coefficient of thermal expansion (CTE) is preferably 5 to 20 ppm / °C, more preferably 8 to 15 ppm / °C, and even more preferably 9 to 12 ppm / °C. Furthermore, from the viewpoint of handling properties and durability of the FPC substrate, the tensile modulus of elasticity in the tensile test of the non-thermoplastic polyimide layer correlates with the coefficient of thermal expansion and is preferably in the range of 5 to 12 GPa. Furthermore, from the viewpoint of handling properties and crack resistance in FPC processing and treatment during tensile testing, the 10% strain stress in the tensile test is preferably 190 to 310 MPa, more preferably 200 to 280 MPa, and even more preferably 210 to 270 MPa.

[0016] Non-thermoplastic polyimide refers to polyimide that, when fixed in film form on a metal frame and heated at a temperature of 450°C for 2 minutes, does not wrinkle or stretch, and maintains its film shape (flat film shape).

[0017] Specific examples of the diamine component used in the non-thermoplastic polyimide layer include 2,2-bis{4-(4-aminophenoxy)phenyl}propane, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, p-phenylenediamine, 4,4'-diaminodiphenylpropane, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfide, 2,2'-dimethyl-4,4'-diaminobiphenyl, 2,2-bis(4-aminophenoxyphenyl)propane, 3,3'-dihydroxy-4,4'-diamino-1,1'-biphenyl, 4,4'-diamino-2,2'-dimethylbiphenyl, 4,4'-diamino-3,3'-dimethylbiphenyl, 4,4'-diamino-3,3'-hydroxybiphenyl, 1,4-diaminobenzene, 1,3-diaminobenzene, 4,4'-bis(4-aminophenoxy), 4,4'-diaminodiphenyl ether, 2,2-bis{4-(4-aminophenoxy)phenyl}propane, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, and the like. From the viewpoints of tensile properties and linear expansion coefficient, p-phenylenediamine (hereinafter sometimes abbreviated as PDA) and 2,2'-dimethyl-4,4'-diaminobiphenyl (hereinafter sometimes abbreviated as m-TB) are preferably used.

[0018] Among these, it is desirable to contain a diamine residue having a biphenyl skeleton (a residue derived from a diamine having a biphenyl skeleton), and the content of the diamine residue having a biphenyl skeleton is preferably 20 mol% or more, more preferably in the range of 20 mol% to 60 mol%, based on all diamine residues constituting the non-thermoplastic polyimide. In particular, it is preferable to use 2,2'-dimethyl-4,4'-diaminobiphenyl.

[0019] Specific examples of the tetracarboxylic dianhydride component are not particularly limited, but aromatic tetracarboxylic dianhydrides are preferred from the viewpoint of heat resistance and the like. Examples include pyromellitic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 4,4'-oxydiphthalic dianhydride, 3,4'-oxydiphthalic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)propane dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)ethane dianhydride, oxydiphthalic dianhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, p-phenylene bis(trimellitic acid monoester anhydride), ethylene bis(trimellitic acid monoester anhydride), bisphenol A bis(trimellitic acid monoester anhydride), and analogs thereof. In particular, at least two selected from pyromellitic dianhydride (hereinafter sometimes abbreviated as PMDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (hereinafter sometimes abbreviated as BPDA), and 3,3',4,4'-benzophenonetetracarboxylic dianhydride (hereinafter sometimes abbreviated as BTDA) are suitably used.

[0020] The tetracarboxylic dianhydride residue desirably contains 3,3',4,4'-benzophenonetetracarboxylic dianhydride and / or 3,3',4,4'-biphenyltetracarboxylic dianhydride, and the content thereof is preferably 40 mol% or more, and may be 100 mol%, based on all dianhydride residues constituting the non-thermoplastic polyimide.

[0021] (Thermoplastic polyimide layer) If the thermoplastic polyimide layer has a high CTE of 65 ppm / °C or higher, the CTE difference with the non-thermoplastic polyimide layer becomes large, leading to differences in shrinkage at the interface during the cooling process after laser drilling, and making residual stress more likely to occur. Therefore, even if the compatibility parameter is 5.0 or lower and the interface compatibility is improved, the crack occurrence rate tends to increase.

[0022] Thermoplastic polyimide refers to polyimide that, when fixed in film form on a metal frame and heated at a temperature of 450°C for 2 minutes, does not wrinkle, stretch, or maintain its film shape.

[0023] The diamines and acidic dianhydrides used in thermoplastic polyimide films are the same as those used in non-thermoplastic polyimide resin layers, but to produce a thermoplastic polyimide film, it is preferable to react a flexible diamine with an acidic dianhydride. Specific examples of flexible diamines include 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene (TPE-R), and 2,2-bis(4-aminophenoxyphenyl)propane (sometimes abbreviated as BAPP).

[0024] Examples of acid dianhydrides that can be suitably combined with these diamines include pyromellitic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, and 4,4'-oxydiphthalic acid dianhydride.

[0025] Among the above combinations of diamine and acid dianhydride, the acid dianhydride preferably contains PMDA as an essential component, and further contains BPDA and / or BTDA, and the diamine preferably contains BAPP and / or TPE-R, and the proportion of these monomers is such that the compatibility parameter (square of the SP value difference) between non-thermoplastic polyimide and thermoplastic polyimide is 5.0 J / cm 3 You should adjust it so that it looks like this:

[0026] (Compatibility parameter SP value difference) The SP values ​​(δ) of each layer, the non-thermoplastic polyimide layer and the thermoplastic polyimide layer, are calculated using Fedors' calculation method, and are given by the following equation δ = (E / V) from the cohesive energy E and molecular capacity V of each component, the diamine component and the acid dianhydride component. 1 / 2 It is calculated as follows. The compatibility parameter (squared difference in SP values) is the square of the difference between the SP value δn of the non-thermoplastic polyimide layer and the SP value δt of the thermoplastic polyimide layer (δn-δt). 2 It is calculated by [this method].

[0027] From the viewpoint of suppressing the rate of crack occurrence, the value of the compatibility parameter between each layer is preferably 5.0 or less, more preferably 4.0 or less, even more preferably 3.0 or less, and particularly preferably 2.0 or less.

[0028] (Film thickness composition of polyimide laminates) The polyimide film laminate (total thickness of each layer) is, for example, 6 μm to 60 μm. The thinner the total thickness of the polyimide film laminate, the easier it is to reduce the weight of the resulting FPC, and the more flexible the resulting FPC becomes. In order to further reduce the weight of the FPC while ensuring mechanical strength and to further improve the flexibility of the FPC, the thickness is preferably 7 μm to 30 μm, and more preferably 10 μm to 25 μm.

[0029] To easily achieve thinning of the FPC while ensuring adhesion to the metal foil, the thickness of the thermoplastic polyimide layer is preferably 1 μm to 15 μm. To easily adjust the coefficient of linear expansion of the polyimide film laminate, the thickness ratio of the non-thermoplastic polyimide layer to the thermoplastic polyimide layer is preferably 55 / 45 to 95 / 5. When multiple non-thermoplastic polyimide layers and thermoplastic polyimide layers are provided, the above thickness ratio is the ratio of the total thickness of each. Even if the number of thermoplastic polyimide layers increases, it is preferable that the total thickness of the thermoplastic polyimide layers does not exceed the total thickness of the non-thermoplastic polyimide layers.

[0030] <Method for manufacturing polyimide laminates and method for manufacturing metal-clad laminates> (Method for manufacturing polyimide laminates) In the present invention, a multilayer polyimide film can be manufactured by simultaneously forming multiple resin layers using a co-extrusion die having multiple channels, or by recovering the polyimide resin layer and then forming a new resin layer on top of it by coating or other means. The former manufacturing method is preferable to improve compatibility between the non-thermoplastic polyimide layer and the thermoplastic polyimide layer and to suppress hole cracks. Since imidization requires very high temperatures, the latter method is preferable to suppress thermal decomposition when providing a resin layer other than polyimide. For example, to obtain a multilayer polyimide film having a thermoplastic polyimide film on at least one side of the polyimide film, the core polyimide precursor and the thermoplastic polyimide precursor can be cast onto a support using a co-extrusion die, and the film can be obtained by carrying out steps iii) and later. When providing a thermoplastic polyimide film by coating, the thermoplastic polyimide precursor can be applied to the non-thermoplastic polyimide layer and then imidization can be performed, or a thermoplastic polyimide solution can be applied and dried.

[0031] (Method for producing polyamic acid) Any known method or a combination thereof can be used to produce polyamic acid, a precursor of polyimide (synthesis method). The characteristic of the polymerization method in the production of polyamic acid lies in the order of monomer addition, and by controlling this order of monomer addition, the various properties of the resulting polyimide can be controlled. When synthesizing polyamic acid using diamines and tetracarboxylic dianhydrides, the desired polyamic acid (polymer of diamines and tetracarboxylic dianhydrides) can be obtained by adjusting the amount of each diamine and the amount of each tetracarboxylic dianhydride (if multiple types of tetracarboxylic dianhydrides are used, the amount of each tetracarboxylic dianhydride). The molar ratio of each residue in the polyimide formed from polyamic acid is, for example, the molar ratio of each monomer (diamine and tetracarboxylic dianhydride) used in the synthesis of polyamic acid. The temperature conditions for the reaction between diamines and tetracarboxylic dianhydrides, i.e., the synthesis reaction of polyamic acid, are not particularly limited, but are, for example, in the range of 20°C to 150°C. The reaction time for the synthesis of polyamic acid is, for example, in the range of 10 minutes to 30 hours. In this embodiment, any method of adding monomers may be used for the production of polyamic acid.

[0032] Typical methods for producing polyamic acid include the following. For example, one method for producing polyamic acid is polymerization by the following steps (Aa) and (Ab) (hereinafter sometimes referred to as "Method A polymerization").

[0033] (Aa): A process to obtain a polymer having amino groups at both ends by reacting an aromatic diamine with an aromatic acid dianhydride in an organic solvent in an excess of aromatic diamine. (Ab): A step in which an aromatic diamine with a different structure from that used in step (Aa) is added, and an aromatic acid dianhydride with a different structure from that used in step (Aa) is added in such a way that the aromatic diamine and aromatic acid dianhydride are substantially equimolar in all steps, and polymerization is carried out.

[0034] Another method for producing polyamic acid is polymerization using the following steps (Ba) and (Bb) (hereinafter sometimes referred to as the "B polymerization method"). (Ba): A step in which an aromatic diamine and an aromatic acid dianhydride are reacted in an organic solvent with an excess of aromatic acid dianhydride to obtain a prepolymer having acid anhydride groups at both ends. (Bb): A step in which an aromatic acid dianhydride with a different structure from that used in step (Ba) is added, and an aromatic diamine with a different structure from that used in step (Ba) is added so that the aromatic diamine and aromatic acid dianhydride are substantially equimolar in the entire process, and polymerization is carried out.

[0035] A synthesis method in which the order of addition is set so that a specific diamine or acid dianhydride reacts selectively with any or a specific diamine or acid dianhydride (for example, polymerization method A and polymerization method B described above) is referred to as sequence polymerization in this specification. Among polymers obtained by sequence polymerization, polymers having two types of segments are called diblock copolymers, and polymers having three types of segments are called triblock copolymers. In contrast, a polymerization method in which the order of addition of diamines and acid dianhydrides is not set (a polymerization method in which monomers react with each other arbitrarily) is referred to as random polymerization in this specification. A polymer obtained by random polymerization is called a random copolymer.

[0036] In this embodiment, sequence polymerization is preferred as a polymerization method for obtaining polyimide that is effective in suppressing film tearing while maintaining the properties of the flexible metal-clad laminate. The weight-average molecular weight of the polyamic acid obtained by the polymerization method described above is preferably in the range of 10,000 to 1,000,000, more preferably in the range of 20,000 to 500,000, and even more preferably in the range of 30,000 to 200,000. If the weight-average molecular weight is 10,000 or more, it becomes easy to form the polyamic acid into a coating film. On the other hand, if the weight-average molecular weight is 1,000,000 or less, it shows sufficient solubility in the solvent, so a coating film with a smooth surface and uniform thickness can be obtained using the polyamic acid solution described later. The weight-average molecular weight used here refers to the polyethylene oxide equivalent value measured using gel permeation chromatography (GPC).

[0037] When obtaining polyimide, a method may be employed in which polyimide is obtained from a polyamic acid solution containing polyamic acid and an organic solvent. Organic solvents that can be used in polyamic acid solutions include, for example, urea-based solvents such as tetramethylurea and N,N-dimethylethylurea; sulfoxide-based solvents such as dimethyl sulfoxide; sulfone-based solvents such as diphenyl sulfone and tetramethyl sulfone; amide-based solvents such as N,N-dimethylacetamide, N,N-dimethylformamide (hereinafter sometimes referred to as "DMF"), N,N-diethylacetamide, N-methyl-2-pyrrolidone, and hexamethyltriamide phosphate; ester-based solvents such as γ-butyrolactone; alkyl halide-based solvents such as chloroform and methylene chloride; aromatic hydrocarbon-based solvents such as benzene and toluene; phenol-based solvents such as phenol and cresol; ketone-based solvents such as cyclopentanone; and ether-based solvents such as tetrahydrofuran, 1,3-dioxolane, 1,4-dioxane, dimethyl ether, diethyl ether, diethylene glycol diethyl ether, diethylene glycol dimethyl ether, and p-cresol methyl ether. These solvents are usually used individually, but two or more may be used in appropriate combinations as needed.

[0038] When polyamic acid is obtained by the polymerization method described above, the reaction solution (solution after the reaction) itself may be used as the polyamic acid solution for obtaining polyimide. In this case, the organic solvent in the polyamic acid solution is the organic solvent used in the reaction in the polymerization method described above. Alternatively, the solid polyamic acid obtained by removing the solvent from the reaction solution may be dissolved in an organic solvent to prepare the polyamic acid solution. Additives such as dyes, surfactants, leveling agents, plasticizers, silicones, and sensitizers may be added to the polyamic acid solution. Fillers may also be added to the polyamic acid solution to improve various properties of the film, such as sliding properties, thermal conductivity, electrical conductivity, corona resistance, and loop stiffness. Any filler may be used, but preferred examples include fillers made of silica, titanium dioxide, alumina, silicon nitride, boron nitride, calcium hydrogen phosphate, calcium phosphate, and mica. The concentration of polyamic acid in the polyamic acid solution is not particularly limited, and is, for example, 5% to 35% by weight, preferably 8% to 30% by weight, based on the total amount of the polyamic acid solution. When the concentration of polyamic acid is between 5% and 35% by weight, an appropriate molecular weight and solution viscosity can be obtained.

[0039] (Method of manufacturing metal-clad laminates) When manufacturing a metal-clad laminate using the polyimide film laminate obtained by the method described above, a metal foil is bonded to at least one side of the polyimide film laminate as described above. The metal foil is not particularly limited, and any metal foil can be used. For example, metal foils made from copper, stainless steel, nickel, aluminum, and alloys of these metals are preferably used. In addition, copper foil such as rolled copper foil and electrolytic copper foil is frequently used in general metal-clad laminates, and copper foil is also preferably used in this embodiment. Furthermore, the metal foil can be used after surface treatment or the like has been applied to adjust the surface roughness, etc., depending on the purpose. In addition, a rust-preventive layer, a heat-resistant layer, an adhesive layer, etc. may be formed on the surface of the metal foil. The thickness of the metal foil is not particularly limited, and any thickness that allows sufficient functionality to be performed according to the application is acceptable.

[0040] (Processing of metal-clad laminates) When forming vias using a metal-clad laminate as the material, the laminate can be cut and a hole can be made by irradiating the area to be processed with a laser. Through holes can be formed by penetrating the metal-clad laminate, or blind vias can be formed by removing only the exposed polyimide layer after removing a portion of the metal foil on the top surface. When forming blind vias, the metal foil on the top surface can be removed with a laser, and then the laser power is reduced to remove the polyimide layer, which allows for stable formation of blind vias.

[0041] Known types of lasers can be used. Short-wavelength lasers such as UV-YAG lasers and excimer lasers are preferred because they exhibit very high absorption rates for both resins and metals. Regarding the formation of through-holes, the method of directly drilling through holes using a drill is also widely used. As for the desmear treatment method after laser processing, known methods can be used, for example, a wet desmear treatment method comprising a swelling step using an alkaline aqueous solution or a solution containing an organic solvent, a roughening step using an alkaline aqueous solution containing sodium permanganate or potassium permanganate, and a neutralization step.

[0042] In the case of double-sided metal-clad laminates, the inner walls of the holes are plated after desmearing to make both sides of the metal-clad laminate electrically conductive. One example of a plating method is to deposit palladium on the inner wall of the hole, and then use the palladium as a nucleus to form an electroless copper plating layer on the inner wall surface. In this case, a plating layer of the desired thickness may be formed by electroless copper plating alone, or a thin electroless copper plating layer may be applied first, followed by electrolytic copper plating to form a plating layer of the desired thickness. [Examples]

[0043] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. The methods for calculating the SP value, coefficient of linear expansion, tensile test, and evaluation of hole crack occurrence rate of polyimide in the synthesis example, examples, and comparative examples are as follows.

[0044] <Rating> (SP value calculation) The calculation is performed using the Fedors method, where δ = (E / V). 1 / 2 It is calculated as follows. δ: SP value E: Cohesive energy (J / mol) V: Molecular capacity (cm 3 / mol) Table 1 shows the calculated cohesive energy and molecular capacity of the acid anhydride and diamine components of polyimide. The SP value of each polyimide layer was calculated from the sum of the cohesive energies and molecular capacities of each component. [Table 1]

[0045] (Coefficient of linear expansion) Using a thermal analyzer (Hitachi High-Tech Science Corporation's "TMA / SS6100"), a polyimide film was heated from -10°C to 400°C under a nitrogen atmosphere, then cooled to -10°C, and then heated again to 400°C. The coefficient of linear expansion was determined from the amount of strain between 100°C and 200°C during the second heating cycle. The measurement conditions are shown below. Sample (polyimide film) size: 3mm wide, 10mm long Load: 1g Heating rate: 10°C / min

[0046] (Tensile test) The stress at 10% strain can be determined from the tensile modulus measurement data. The tensile modulus was measured according to ASTM D882. The measurements were taken using a Shimadzu AUTOGRAPH AGS-J under conditions of 23°C and 55% RH. Sample measurement range: 15 mm Distance between gripping parts: 100 mm Tensile speed: 200 mm / min

[0047] (Hole crack test) In the examples and comparative examples described later, electrolytic copper foil (3EC-M3S-HTE, manufactured by Mitsui Mining & Smelting Co., Ltd.) with a thickness of 12 μm was placed on both sides of the multilayer polyimide film. Furthermore, a protective film (Apical® 125NPI, manufactured by Kaneka Corporation, thickness: 125 μm) was placed on the outer surface of each electrolytic copper foil. Lamination was then performed at a lamination temperature of 360°C, a lamination pressure of 265 N / cm (27 kgf / cm), and a lamination speed of 1.0 m / min to obtain a flexible copper-clad laminate. Next, the obtained flexible copper-clad laminate was cut into a rectangular shape of 5.0 cm × 20.0 cm to obtain a sample for processing. Then, using a UV-YAG laser, blind vias (10 x 10 = 100, spacing: 1 mm) with a diameter of 75 μm were formed on the sample for processing under the laser processing conditions described in Table 2. [Table 2]

[0048] Next, the laser-processed samples were subjected to desmear treatment under the conditions shown in Table 3, and then the copper foil was removed by etching to obtain evaluation samples. The chemicals used for the desmear treatment were all manufactured by MacDermid Performance Solutions Japan Co., Ltd. In addition, water washing was performed between the swelling and roughening processes, between the roughening and neutralization processes, and after the neutralization process. [Table 3]

[0049] The obtained evaluation samples were then observed under crossed nicols at 200x magnification using a polarizing microscope to determine the presence or absence of cracks. Specifically, a condition in which light leakage occurred around the hole was judged as "crack present." After observing 100 holes, the percentage of holes with cracks (crack occurrence rate) was calculated as a percentage. Figures 1 and 2 show examples of polarizing microscope images used for actual determination. Figure 1 is an example of a hole without cracks because there was no light leakage around the hole. Figure 2 is an example of a hole with cracks because there was light leakage around the hole. For holes where the degree of light leakage was weak and the presence or absence of cracks could not be determined, the cross-section of the hole was observed using an electron microscope to determine the presence or absence of cracks.

[0050] The abbreviations for the diamines and acidic dianhydrides used in the synthesis of polyamic acids are listed below. (Diamine) PDA: Paraphenylenediamine ODA: 4,4'-diaminodiphenyl ether m-TB: 2,2'-dimethyl-4,4'-diaminobiphenyl BAPP: 2,2-Bis{4-(4-aminophenoxy)phenyl}propane TPE-R: 1,3-bis(4-aminophenoxy)benzene (acid dianhydride) PMDA: Pyromellitic dianhydride BPDA: 3,3',4,4'-biphenyltetracarboxylic acid dianhydride BTDA:3,3',4,4'-benzophenonetetracarboxylic dianhydride ODPA: 4,4'-Oxydiphthalic acid dianhydride

[0051] <Synthesis Example 1: Polyamic acid solution for non-thermoplastic polyimides> 326.01 g of dimethylformamide (DMF) and 23.83 g of m-TB were placed in a 2 L glass flask. Then, while stirring the contents of the flask, 35.09 g of BTDA was gradually added to the flask. After visually confirming that the BTDA had dissolved, the contents of the flask were stirred for another 30 minutes. Next, while stirring the contents of the flask, a pre-prepared BTDA solution (solvent: DMF, amount of dissolved BTDA: 1.09 g, BTDA concentration: 7.2 wt%) was added to the flask. When adding the BTDA solution to the flask, it was added gradually to prevent a rapid increase in the viscosity of the contents of the flask. When the viscosity of the contents of the flask at a temperature of 23°C reached 2000 poise, the addition of the PMDA solution and stirring of the contents of the flask were stopped to obtain solution P1, a polyamic acid solution for non-thermoplastic polyimides.

[0052] <Evaluation of non-thermoplastic polyimides> To solution P1, a polyamic acid solution for non-thermoplastic polyimide described above, an imidation accelerator consisting of acetic anhydride, isoquinoline, and DMF (adjusted so that the acetic anhydride / isoquinoline ratio was 3.00 / 0.74 relative to the polyamic acid terminal molar ratio) was added at a weight ratio of 40%, continuously stirred, and cast onto aluminum foil. After heating this resin film at 110°C for 150 seconds, the self-supporting gel film was peeled off the aluminum foil and fixed on all four sides onto a pin frame. It was dried and imidized at 250°C for 17 seconds and 350°C for 70 seconds to produce a non-thermoplastic polyimide film with a thickness of 17 μm. The physical properties of the non-thermoplastic polyimide film were evaluated, and the results are shown in Table 4. In Table 4, the applicability to copper-clad laminates was indicated by ○ if it matched the elastic modulus of 5-12 GPa, 10% strain stress of 190-310 MPa, and coefficient of linear expansion of 5-20 ppm / °C obtained by tensile testing of a single layer of non-thermoplastic polyimide, and × if it did not match.

[0053] <Synthesis Examples 2-4 and Comparative Examples 1-8: Polyamic acid solutions for non-thermoplastic polyimides> Similar to Synthesis Example 1, each monomer was reacted at the monomer proportions (mol%) shown in Table 4 to synthesize polyamic acid solutions (P2-P12) for non-thermoplastic polyimides. For P3, 4, and 10, sequence polymerization was performed, with the diamine component followed by the acid dianhydride component in the order of the first sequence reaction, followed by the second sequence reaction to synthesize the polyamic acid solution. In the second sequence, the acid anhydride component was added in the order of BTDA / or BPDA followed by PMDA. Similar to Synthesis Example 1, non-thermoplastic polyimide films were prepared, and the evaluation results are shown in Table 4. [Table 4]

[0054] <Synthesis Example 5: Polyamic Acid Solution for Thermoplastic Polyimide> 335.84 g of DMF, 26.83 g of TPE-R, and 1.03 g of m-TB were placed in a 2 L glass flask. Then, while stirring the contents of the flask, 21.82 g of BTDA was gradually added to the flask. After visually confirming that the BTDA had dissolved, the contents of the flask were stirred for a further 60 minutes. After stirring, 5.70 g of PMDA was gradually added to the flask. After visually confirming that the PMDA had dissolved, the contents of the flask were stirred for a further 30 minutes. Next, while stirring the contents of the flask, a pre-prepared PMDA solution (solvent: DMF, amount of PMDA dissolved: 0.63 g, PMDA concentration: 7.2 wt%) was added to the flask. When adding the PMDA solution to the flask, it was added gradually to prevent a rapid increase in the viscosity of the contents of the flask. When the viscosity of the contents of the flask at a temperature of 23°C reached 2000 poise, the addition of the PMDA solution and stirring of the contents of the flask were stopped to obtain solution W1, a thermoplastic polyamic acid solution.

[0055] <Synthesis Examples 6-27: Polyamic Acid Solutions for Thermoplastic Polyimides> Similar to Synthesis Example 7, each monomer was reacted in the proportions (mol%) shown in Table 5 to synthesize polyamic acid solutions (W2-W23) for thermoplastic polyimides. For W10, 22, and 23, the polyamic acid solution was synthesized by adding the second sequence after the first sequence reaction, in the order of diamine component followed by acid dianhydride component. [Table 5]

[0056] (Example 1) To the polyamic acid solution (P1) for non-thermoplastic polyimide obtained in Synthesis Example 3, an imidation accelerator consisting of acetic anhydride, isoquinoline, and DMF (the acetic anhydride / isoquinoline ratio was adjusted to 2.00 / 0.74 relative to the polyamic acid terminal molar ratio) was added at a weight ratio of 40% to the polyamic acid solution, and the mixture was continuously stirred. The polyamic acid solution (W17) for thermoplastic polyimide obtained in Synthesis Example 21 was then cast onto aluminum foil with a thickness of thermoplastic / non-thermoplastic / thermoplastic = 60 μm / 330 μm / 40 μm. After heating this resin film at 120°C for 200 seconds, the self-supporting gel film was peeled off the aluminum foil and fixed on all four sides onto a pin frame. The film was then dried and imidized at 250°C for 17 seconds and 350°C for 70 seconds to obtain a polyimide film with a thickness of 25 μm.

[0057] (Examples 2-14, Comparative Examples 1-15) Similar to Example 1, a polyimide film with a thickness of 25 μm was obtained using the combination of the polyamic acid solution for non-thermoplastic polyimide and the polyamic acid solution for thermoplastic polyimide shown in Table 6. [Table 6]

[0058] <Evaluation Results> (Non-thermoplastic polyimide layer) When Synthesis Examples 1 to 4 are used as the non-thermoplastic polyimide layer, the resulting thermoplastic / non-thermoplastic / thermoplastic multilayer polyimide achieves a good balance between the mechanical strength and CTE of the film, making it optimal as a polyimide film for FPC. When Comparative Synthesis Examples 1 to 8 are used, the overall CTE of the resulting thermoplastic / non-thermoplastic / thermoplastic multilayer polyimide layer becomes too low or too high, leading to deteriorated dimensional stability, which is unsuitable. Further, even if the overall CTE is adjusted by modifying the thickness of the thermoplastic polyimide layer, the mechanical strength cannot be balanced, making it unsuitable for use as a copper-clad laminate.

[0059] (Thermoplastic / non-thermoplastic / thermoplastic polyimide laminate) As the non-thermoplastic polyimide layer, the polyamic acid solutions (P1 to P4) for non-thermoplastic polyimide synthesized in Synthesis Examples 1 to 4 and the polyamic acid solutions for thermoplastic polyimide prepared in Synthesis Examples 5 to 27 were used to produce thermoplastic / non-thermoplastic / thermoplastic three-layer films, and the effects of the hole crack occurrence rate and the SP value difference were investigated.

[0060] When various combinations of non-thermoplastic / thermoplastic materials are used in Examples 1 to 14, it was found that the occurrence rate decreases to 50% or less when the SP value difference between the non-thermoplastic and thermoplastic layers is 5 J / cm 3 or less. It was also found that in Comparative Examples 1 to 12 and 15, when the SP value difference is 5 J / cm 3 or more, the hole crack occurrence rate tends to increase to 60% or more. This result is considered to indicate that reducing the SP value difference between the non-thermoplastic polyimide layer and the thermoplastic polyimide layer improves interfacial compatibility and enhances mechanical strength. However, in Comparative Examples 13 and 14, even though the SP value difference is 5 J or less, the hole crack occurrence rate is as high as 100%. The increased CTE difference between the non-thermoplastic and thermoplastic layers increases residual stress during cooling after laser drilling, and when the film strength is reduced by desmear treatment, the film cannot withstand the residual stress, which manifests as cracks. From these results, it was clarified that hole cracks can be suppressed by not excessively widening the CTE difference between the thermoplastic and non-thermoplastic layers and reducing the SP value difference.

Claims

1. This polyimide laminate comprises a non-thermoplastic polyimide with a thermoplastic polyimide layer on at least one side, wherein the non-thermoplastic polyimide single layer has an elastic modulus of 5 to 12 GPa, a 10% strain stress of 190 to 310 MPa, and a coefficient of thermal expansion of 5 to 20 ppm / °C as determined by tensile testing, and the compatibility parameter (square of the SP value difference) between the non-thermoplastic polyimide and the thermoplastic polyimide is 5.0 J / cm². 3 The following conditions apply, and the coefficient of linear expansion of the thermoplastic polyimide is 65 ppm / °C or less: A polyimide film laminate characterized in that the aromatic diamine used in the production of the non-thermoplastic polyimide comprises paraphenylenediamine, 4,4'-diaminodiphenyl ether, and 2,2'-dimethylbiphenyl-4,4'-diamine.

2. The polyimide film laminate according to claim 1, characterized in that the acid dianhydride used in the production of the non-thermoplastic polyimide comprises 3,3',4,4'-benzophenonetetracarboxylic dianhydride and / or 3,3',4,4'-biphenyltetracarboxylic dianhydride.

Citation Information

Patent Citations

  • Multilayer polyimide film

    JP2010115797A

  • Polyimide laminate film

    JP2017177604A

  • Polyimide film

    JP2017179149A

  • Laminate, printed wiring board and method for manufacturing them

    WO2004050352A1

  • Multilayer polyimide film, laminate and metal-clad laminate

    WO2009019968A1